Biochemical characterisation and small molecule modulation of the interaction between two cytosolic Hsp70s from Trypanosoma brucei and potential co-chaperones - Bentley, Stephen John (Rhodes University, Faculty of Science, Biotechnology Innovation Centre, 2018)
Expected release date-April 2019
Keywords: Uncatalogued